2018
DOI: 10.1007/s00894-018-3691-y
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing ZnO clusters through the density-functional theory

Abstract: The potential energy surface of Zn O clusters (n = 2, 4, 6, 8) has been explored by using a simulated annealing method. For n = 2, 4, and 6, the CCSD(T)/TZP method was used as the reference, and from here it is shown that the M06-2X/TZP method gives the lowest deviations over PBE, PBE0, B3LYP, M06, and MP2 methods. Thus, with the M06-2X method we predict isomers of Zn O clusters, which coincide with some isomers reported previously. By using the atoms in molecules analysis, possible contacts between Zn and O a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Earlier work has demonstrated that the drum conformation (two hexagonal ring layers) represents the global minimum geometry of (MX) 6 [34,42,43]. Our own calculations confirm this preference, with some qualifications.…”
Section: Isolated Quantum Dotssupporting
confidence: 78%
See 1 more Smart Citation
“…Earlier work has demonstrated that the drum conformation (two hexagonal ring layers) represents the global minimum geometry of (MX) 6 [34,42,43]. Our own calculations confirm this preference, with some qualifications.…”
Section: Isolated Quantum Dotssupporting
confidence: 78%
“…Other studies have been concerned chiefly with conformational analysis of various QDs [42,43]. Among various possible configurations of (ZnO) 6 , the Bdrum^(two parallel stacked six-membered rings) conformer is most stable.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to Wurtzite-glucose with the effect of the Cu atom, Zn–O stretching peaks in Cu-Wurtzite-glucose ( 8 ) were detected at higher frequencies [ 55 , 59 ]. In the structure of the Rocksalt-glucose complex ( 9 ), it is seen that the cubic structure of the metal oxides (Zn 4 O 4 ) turns into an s-shaped structure [ 62 ]. However, in the Cu-Rocksalt-glucose complex ( 10 ), it is observed that the Cu–Zn 3 O 4 metal oxide cubic structure is not completely destroyed, but the O atom (Zn 2 O–H) in the cubic structure forms three bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The development of the family of M06 hybrid functionals is important for a range of applications in materials science [24], based on the results of calculations of ZnO structures and structural analysis, it is applied to different methodologies where it is observed that it produces high accuracy. The way to know the correspondence of a three-dimensional structure is done by means of geometry optimization calculations to determine the minimum energy structure [25].…”
Section: Methodsmentioning
confidence: 99%